Impact of Community-Led Total Sanitation and Hygiene on Prevalence of Diarrheal Disease and Associated Factors among Under-Five Children: A Comparative Cross-Sectional Study in Selected Woredas of Gamo Gofa Zone, Southern Ethiopia. (24th February 2020) - Ashole Alto, Agune; Godana, Wanzahun; Gedamu, Genet
Abstract : Background . Diarrheal diseases are still one of the major causes of morbidity in under-five children in sub-Saharan Africa. In Ethiopia, diarrhea is responsible for 9% of all deaths and is the major cause of under-five mortality. Objective . To assess the impact of community-led total sanitation and hygiene on the prevalence of diarrheal disease and factors associated among under-five children in Gamo Gofa Zone. Methods . Community-based comparative cross-sectional study design was used to compare the impact of community-led total sanitation and hygiene intervention on under-five diarrheal disease. Multistage sampling method was employed. The data were collected by using pretested structured questionnaires. Data quality was ensured by daily supervision completeness and consistency. The data were coded, entered, and cleaned by using Epi Info version 7 and were analyzed by using SPSS version 20. Bivariate and multivariable analyses were carried out by using binary logistic regression. Significance was declared by using p value of <0.05 and AOR with 95% confidence intervals. Results . The response rate of this study was 93.3%. The overall diarrhea prevalence was 27.5% (CI = (24.06, 30.97)) which was 18.9% (CI = (14.94, 23.2)) in implemented and 36.2%. (CI = (30.41, 41.59)) in nonimplemented woredas. Children whose age was between 12 and 23 months (AOR = 1.6) and greater than 24 months (AOR = 5), availability of handwashing facilities (AOR = 4), disposal of waste in open field (AOR = 9.7), unimproved source of drinking water (AOR = 6.5), using only water for handwashing (AOR = 6), children who started complementary feeding less than 6 months (AOR = 5.6) and greater than 6 months (AOR = 5.2), and utensils used to feed children such as bottle (AOR = 3.9) were the factors positively associated with diarrhea. Conclusion . The overall prevalence of under-five diarrhea was 27.5%. The prevalence was low in CLTSH woredas as compared with non-CLTSH woredas. The study showed that handwashing facility, using only water for handwashing, open refuse disposal, and unimproved source of drinking water among under-five had a statistically significant association with diarrhea occurrence in CLTSH nonimplemented areas. Integrated efforts are needed from the Ministry of Health together with the WASH Project in improving drinking water, handwashing facilities, and solid waste disposal practices.